TRUST AND USER SATISFACTION IN DIGITAL APPLICATION: AN ANALYSIS OF GOPAY E-MONEY SERVICE - Candra Gunawan; Eka Febriani; Angga Kusumah (JASS (Journal of Accounting for Sustainable Society), 2024)
The digital era has an impact on people's economic activities which provide convenience, speed and accuracy in financial transactions, one of which is e-money, where the GoPay application is an e-money application that offers convenience and security in various digital payment transactions. The aim of the research is to analyze the influence of security, information quality, and system quality on the trust and satisfaction of users of the GoPay e-money application. Researchers collected 350 samples by distributing questionnaires to GoPay application users. The research results show that security, information quality, and system quality significantly influence trust and satisfaction of users. Keywords: security, information quality, system quality, trust, satisfaction of users